H‐Shaped Oligofluorenes for Highly Air‐Stable and Low‐Threshold Non‐Doped Deep Blue Lasing. (24th March 2014) - Qian, Yan; Wei, Qi; Del Pozo, Gonzalo; Mróz, Marta M.; Lüer, Larry; Casado, Santiago; Cabanillas‐Gonzalez, Juan; Zhang, Qi; Xie, Linghai; Xia, Ruidong; Huang, Wei
<x xml:space="preserve">Abstract</x> H‐shaped oligofluorenes as gain media exhibit excellent photo‐ (large robustness against oxidation) and thermal stabilities in ambient atmosphere for large σe and low‐threshold (0.22 nJ pulse−1) deep blue distributed feedback (DFB) lasers. Their amplified spontaneous emission (ASE) thresholds increase less than 3‐fold and the emission spectra exhibit almost no shift with film samples annealed up to 200 °C in open air. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>